Crystal structure of 3-(thiophen-2-yl-carbonyl)-4-(thiophen-2-yl)-1-isopropyl-4-piperidinol, C17H21NO2S2 - Aydin Abdullah; Akkurt Mehmet; Gul Halise Inci; Mete Ebru; Sahin Ertan (Zeitschrift für Kristallographie - New Crystal Structures, 2013)
C17H21NO2S2, P1̅ (no. 2), a = 5.9254(2) Å, b = 8.9579(2) Å, c = 16.6787(4) Å, α = 92.570(1)°, β = 99.158(2)°, γ = 98.441(2)°, V = 862.4 Å3, Z = 2, Rgt(F) = 0.0557, wRref(F2) = 0.1477, T = 293 K.